Design and Analysis of a Kind of Self- lock Pole- climbing Robot - Wang Caidong; Fan Guofeng; Wang Xinjie; Tang Yiming (Jixie chuandong)
According to the problem of the loading capacity is limited and the accidental injury is easy happened,a self- lock pole- climbing robot is designed based on self- lock principle. The structure scheme and working principle of the robot are introduced. The self- locking conditions and motion stability are analyzed. The carrying capacity of robot is calculated. The control method for the robot climbing on variable diameter pole is analyzed. The results show that the robot can climb variable diameter pole stably,which meets the requirements for telegraph pole aerial work.